Lost cities, ancient tombs : 100 discoveries that changed the world - Williams, A. R.; Hiebert, Fredrik T. (National Geographic, 2021)
"The story of human civilization, as told through 100 key discoveries spanning six continents, including firsthand reports from explorers, scientists, and antiquarians"--